50,000 years of genetic uniformity in the critically endangered Iberian lynx - Rodriguez, R; Ramirez, O; Valdiosera, CE; Garcia, N; Alda, F; Madurell-Malapeira, J; Marmi, J; Doadrio, I; Willerslev, E; Gotherstrom, A; Arsuaga, JL; Thomas, MG; et al. (WILEY-BLACKWELL, 2011)
Low genetic diversity in the endangered Iberian lynx, including lack of mitochondrial control region variation, is thought to result from historical or Pleistocene/Holocene population bottlenecks, and to indicate poor long-term viability. We find no variability in control region sequences from 19 Iberian lynx remains from across the Iberian Peninsula and spanning the last 50 000 years. This is best explained by continuously small female effective population size through time. We conclude that low genetic variability in the Iberian lynx is not in itself a threat to long-term viability, and so should not preclude conservation efforts.